2010
DOI: 10.1021/jp1021505
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Symmetry Measures of Density Maps

Abstract: Density maps are commonly used for data presentation, and their symmetry is a central characteristic. Quite often near symmetry can be detected but not the exact one. Here we present a method for estimating the symmetry content of density maps. We thus extend the application of the continuous symmetry measure (CSM) methodology to many-points problems. We demonstrate the applicability of the method on electron-density probability maps and use, as a model, a series of copper clusters: 1Cu3 +, 1Cu4 (planar and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In particular these results suggest that in concerted reactions one can find a minimal symmetry measure value that is not necessarily zero (i.e., ideally symmetric), with respect to the original expected symmetry, and that higher reactivity in such reactions is associated with lower CSM values, that is, with higher quantitative symmetry values. Finally, we draw attention to a recent study by Casanova et al, who suggested a symmetry measure of the electron density , that could be suitable to test the influence of substitution on the orbital symmetry of concerted reactions; extension of our nuclei geometry analysis to orbitals analysis by this and by related methods , is in progress.…”
Section: Discussionmentioning
confidence: 98%
“…In particular these results suggest that in concerted reactions one can find a minimal symmetry measure value that is not necessarily zero (i.e., ideally symmetric), with respect to the original expected symmetry, and that higher reactivity in such reactions is associated with lower CSM values, that is, with higher quantitative symmetry values. Finally, we draw attention to a recent study by Casanova et al, who suggested a symmetry measure of the electron density , that could be suitable to test the influence of substitution on the orbital symmetry of concerted reactions; extension of our nuclei geometry analysis to orbitals analysis by this and by related methods , is in progress.…”
Section: Discussionmentioning
confidence: 98%
“…(2). Here, we adopt the approach of Pinsky et al52 and we further develop it as follows. (1) Apply the symmetry operation once, using the symmetry element found in the Section “Finding an Initial Position for the Symmetry Element.” Two sets of points are thus obtained: the original set, X, and the set obtained by the operation, Y.…”
Section: The Methodologymentioning
confidence: 99%
“…The continuous symmetry measure (CSM) methodology33–54 will be used in this article, because it is simple and versatile. The CSM is the normalized distance between the original structure and the closest symmetrical object.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The holographic electron density theorem has important role in local shape analysis, in drug design, , in toxicological risk assessment, and in the prediction of “latent properties”, for example, excited state properties not exhibited in the ground electronic ground state, , and in a wide range of additional applications by various authors. , …”
Section: Applications Of the Holographic Electron Density Theorem To ...mentioning
confidence: 99%